Microbiome Sample Comparison and Search: From Pair-Wise Calculations to Model-Based Matching - Zha, Yuguo; Chong, Hui; Ning, Kang (Frontiers in Microbiology, 2021)
A huge quantity of microbiome samples have been accumulated, and more are yet to come from all niches around the globe. With the accumulation of data, there is an urgent need for comparisons and searches of microbiome samples among thousands of millions of samples in a fast and accurate manner. However, it is a very difficult computational challenge to identify similar samples, as well as identify the likely origins, among such a grand pool of samples from all around the world. Currently, several approaches have already been proposed for such a challenge, based on either distance calculation, unsupervised algorithms, or supervised algorithms. These methods have advantages and disadvantages for different settings of comparisons and searches, and their results are also drastically different. In this review, we systematically compared distance-based, unsupervised, and supervised methods for microbiome sample comparison and search. Firstly, we have assessed their accuracy and efficiency, both in theory and in practice. Then we have described the scenarios in which one or multiple methods are suitable to be applied for sample searches. Thirdly, we have provided several applications of microbiome sample comparison and search, and provided suggestions on the choice of methods. Finally, we have provided several perspectives for the future development of microbiome sample comparison and search, including deep learning technologies for tracking the sources of microbiome samples.